2007
DOI: 10.1073/pnas.0610719104
|View full text |Cite
|
Sign up to set email alerts
|

Niche characteristics explain the reciprocal invasion success of stream salmonids in different continents

Abstract: An ability to understand and predict invasions is elemental for controlling the detrimental effects of introduced organisms on native biota. In eastern North America, European brown trout generally dominates over, and eventually replaces, the native brook trout. We show here that in northern Europe the pattern of replacement between these two species is reversed: when transferred to North European streams, brook trout spread extensively and partially replaced the native brown trout. The effect of brook trout o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
77
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 35 publications
10
77
1
Order By: Relevance
“…Also, as in North America (Flebbe 1994;Essington et al 1998) and elsewhere in Europe (Korsu et al 2007), brook trout in our study stream used the upstream (i.e., pool-like) sections of the stretch while brown trout was in the downstream (i.e., riffle-like) sections, with an overlap area located in the middle of the studied stretch. In term of spawning micro-habitat, brown trout is known to use spawning sites with high flows, while brook trout preferentially use deep sites with lower flow (Witzel and MacCrimmon 1983;Essington et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, as in North America (Flebbe 1994;Essington et al 1998) and elsewhere in Europe (Korsu et al 2007), brook trout in our study stream used the upstream (i.e., pool-like) sections of the stretch while brown trout was in the downstream (i.e., riffle-like) sections, with an overlap area located in the middle of the studied stretch. In term of spawning micro-habitat, brown trout is known to use spawning sites with high flows, while brook trout preferentially use deep sites with lower flow (Witzel and MacCrimmon 1983;Essington et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Because the genetic stocks of brown trout are considered as tbreatened in many parts of Europe (Almodovar and Nicola 2004), the populations that still remain in headwater streams have high conservation value for the species. However, this is where brown trout is most likely to be affected by the presence of brook trout (Korsu et al 2007). Consequently, more attention should be paid to the effects of brook trout on brown trout reproduction in Europe and to its long-term consequences on natura1 population ecology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Finland, brook trout are mostly established in tributary streams, where they may form dense populations that can be harmful to local brown trout populations (Korsu et al 2007, Korsu & Huusko 2009). They found that propagule pressure in terms of the number of individuals released and introduction events leading to highly successful establishment of brook trout, came to about 8000 individuals.…”
Section: Discussionmentioning
confidence: 99%